Prawo ludów rdzennych do samostanowienia w świetle „Deklaracji Narodów Zjednoczonych o prawach ludów rdzennych” - Bonusiak, Grzegorz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
The UN Declaration on the Rights of Indigenous Peoples states that "Indigenous peoples have the right to self-determination. By virtue of that right they freely determine their political status and freely pursue their economic, social and cultural development." This paper is an attempt to examine whether indigenous peoples are analogous to the concept of peoples present in international law and the precise scope of their right to self-determination.
The indigenous peoples right to self-determination in the light of the United Nations Declaration on the rights of indigenous peoples
Keywords: indigenous peoples; self-determination; collective rights